The Mediating Role of Teacher Effective Communication on the Relationship between Students’ Mathematics Interest and their Mathematics Performance - Paul Agmabire Akendita; Francis Ohene Boateng; Yarhands Dissou Arthur; Gideon Mensah Banson; Maccarthy Abil; Marfo Ahenkorah (EDUPEDIA Publisher, 2025)
The study investigated how teacher-effective communication mediated the relationship between students’ mathematics interest and performance. The descriptive survey design, which is anchored on the quantitative research approach of the positivism paradigm, was used, and 200 second-year students of a Senior High School in the Talensi district of the Upper East Region were selected through the means of stratified sampling procedures as well as random selections from the strata. A structural equation model (SEM) with bootstrap samples was used to analyze the gathered data, and it was discovered that students' performance in mathematics was positively and statistically impacted significantly on their interest in the subject. In addition, teacher-effective communication was found to have a significant direct positive statistical effect on students’ mathematics performance. Furthermore, students’ mathematics interests correlated positively with the teacher's effective communication. The findings indicated that there existed a partial mediation effect of teacher-effective communication on the relationship between students’ mathematics interest and students’ mathematics performance. Teachers should be allowed to grow professionally in teaching mathematics to communicate vividly and efficiently in mathematical concepts. This will strengthen their mathematical communication skills and also imbibe in them the abilities to incorporate different kinds of collaborative learning techniques to aid students in making faster progress in their mathematical proficiency.